Effect of soft tissue on dissipating energy & reducing forces - Pain, M. T. G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
During impacts the soft tissues of the body move relative to the underlying skeleton and so the rigid body approximation used in most whole body biomechanical analysis can have limitations. Quantifying both the characteristics of the soft tissue motion and then its effects on joint moments and forces, as well as the forces and energy within the soft tissues themselves can be important for a fuller understanding of impact dynamics. During this part of the applied session examples from both modelling and experimental based research will be presented that demonstrate some of the effects soft tissue motion has on the system dynamics.